The Global informal workforce : priorities for inclusive growth - Delechat, Corinne; Medina, Leandro (Washington, D.C International Monetary Fund (IMF), 2021)
The Global Informal Workforce is a fresh look at the informal economy around the world and its impact on the macroeconomy. The book covers interactions between the informal economy, labor and product markets, gender equality, fiscal institutions and outcomes, social protection, and financial inclusion. Informality is a widespread and persistent phenomenon that affects how fast economies can grow, develop, and provide decent economic opportunities for their populations. The COVID-19 pandemic has helped to uncover the vulnerabilities of the informal workforce. (IMF page)
Introduction: What Do We Know About the Informal Economy? -- Chapter 1 The Evolution of Shadow Economies through the 21st Century -- Chapter 2 Europe’s Shadow Economies: Estimating Size and Outlining Policy Options -- Chapter 3 Nonlinearity between the Shadow Economy and Economic Development -- Chapter 4 The Effect of Regulatory Policy on Firm Growth in Sub-Saharan Africa -- Chapter 5 Informality and Labor Market Dynamics in Latin America -- Chapter 6 Immigration and Employment: Substitute versus Complementary Labor in Selected African Countries -- Chapter 7 The Close Relationship between Informality and Gender Gaps in Sub-Saharan Africa -- Chapter 8 How Institutions Shape the Informal Economy -- Chapter 9 National and Subnational Tax Reforms to Address Informality -- Chapter 10 Beyond the COVID-19 Crisis: A Framework for Sustainable Government-to-Person Mobile Money Transfers -- Chapter 11 Macroprudential Policies and Financial Inclusion: Good Intentions and Unintended Consequences -- chapter 12 Financial Inclusion, Bank Competition, and Informal Employment in Sub-Saharan Africa
includes bibliographical references and index
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMICS; INFORMAL SECTOR; LABOUR MARKET; ECONOMIC GROWTH